Farewell to the iconic 'libraries - Abd Razak, Dzulkifli (2006)
An African saying likens a learned person to a proverbial library. "When a learned dies, a library is burned down," goes the proverb. In the last few weeks, at least three such "libraries" burned down, one of which was our very own. On Sept 6, Tan Sri Balachandra Chakkingkal Sekhar, fondly known as Mr Natural Rubber, Malaysia's worldfamous pioneer rubber researcher, passed away. He was the first Malaysian to head the Rubber Research Institute (RRI) Malaysia, and later was made the chairperson of the Malaysian Rubber Research Development Board. He died of a heart attack at the age of 76 when he was in Chennai, India, as a visiting professor of Anna University to pursue his lifetime passion—rubber research.